From the Veins to the Heart: A Rare Cause of Varicose Veins - Michele Dalla Vestra; Elisabetta Grolla; Luca Bonanni; Vittorio Dorrucci; Fabio Presotto; Fausto Rigo (Case Reports in Vascular Medicine)
The presence of pulsating varicous veins is an uncommon finding, generically attributed to right heart failure. The precise causes of this phenomenon have been poorly defined in the literature. The finding of this infrequent condition is important because it may be a sign of major diseases, often not known. Here we described a 75-year-old woman presented to the Angiology Unit for the presence of bilateral pulsatile swelling in her groin and along both lower limbs. A bedside ultrasound examination showed an arterial like pulsating flow both in the superficial and in the deep veins of the lower limbs due to a severe tricuspid regurgitation not previously known.